A new platform for autoimmune diseases. Inducing tolerance with liposomes encapsulating autoantigens - Almenara-Fuentes, Lidia; Rodriguez-Fernandez, Silvia; Rosell-Mases, Estela; Kachler, Katerina; You, Axel; Salvado, Miriam; Andreev, Darja; Steffen, Ulrike; Bang, Holger; Bozec, Aline; Schett, Georg; Le Panse, Rozen; et al. (Nanomedicine : nanotechnology, biology, and medicine, 2023)
Autoimmune diseases (AIDs) are caused by the loss of self-tolerance and destruction of tissues by the host's immune system. Several antigen-specific immunotherapies, focused on arresting the autoimmune attack, have been tested in clinical trials with discouraging results. Therefore, there is a need for innovative strategies to restore self-tolerance safely and definitively in AIDs. We previously demonstrated the therapeutic efficacy of phosphatidylserine (PS)-liposomes encapsulating autoantigens in experimental type 1 diabetes and multiple sclerosis. Here, we show that PS-liposomes can be adapted to other autoimmune diseases by simply replacing the encapsulated autoantigen. After administration, they are distributed to target organs, captured by phagocytes and interact with several immune cells, thus exerting a tolerogenic and immunoregulatory effect. Specific PS-liposomes demonstrate great preventive and therapeutic efficacy in rheumatoid arthritis and myasthenia gravis. Thus, this work highlights the therapeutic potential of a platform for several autoimmunity settings, which is specific, safe, and with long-term effects.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Autoimmune diseases; Immunotherapy; Myasthenia gravis; Nanomedicine; Preclinical mouse models; Rheumatoid arthritis